Journey toward freedom; the story of Sojourner Truth. - Bernard, Jacqueline, 1921-1983. (New York, Norton, 1967)
Biography of Sojourner Truth, who was born into slavery, freed in 1827, and became famous for her courage, quick wit, and ready challenge as she campaigned for abolition and women's rights in New York and the Midwestern States.
Bibliography: p. [255]-259.
Keywords: Truth Sojourner -- d 1883; Truth Sojourner -- d 1883; Social reformers; Abolitionists; African American abolitionists -- United States